Canal of Nuck hydrocele - Michael Kochis; Allan M. Goldstein; Cornelia Griggs (Elsevier, 2021)
Background: The canal of Nuck describes a rare defect of the female inguinal canal that predisposes to the development of hernias or hydroceles. We present the case of a 12-month-old girl with a right inguinal mass representing a hydrocele of the canal of Nuck and review the reported cases in the literature to characterize the typical presentation of this uncommon pathology. Methods: We performed a systematic review of the literature to identify reports of canal of Nuck hydroceles in females age 13 years and below. Data on presenting symptoms, workup, and treatment were analyzed. Results: The review identified a total of 105 cases dating back to the 1890s. Incidence was progressively less common with age. The hydroceles were mostly right-sided (66%), nontender (75%), non-reducible (88%), mobile (86%), and transilluminating (89%). Ultrasound featured in most workups, and MRI was occasionally used. Only 60% of reports mentioning preoperative differential diagnoses indicated suspicion for hydrocele. Open surgical excision is the standard treatment approach. Conclusions: Canal of Nuck hydrocele is a rare pathology that should be on the differential diagnosis for a girl with an inguinal mass. Understanding the typical presentation will help clinicians achieve an accurate diagnosis.